Cardiac Restoration Stemming From the Placenta Tree: Insights From Fetal and Perinatal Cell Biology - Bollini, Sveva; Silini, Antonietta R.; Banerjee, Asmita; Wolbank, Susanne; Balbi, Carolina; Parolini, Ornella (Frontiers in Physiology, 2018)
Efficient cardiac repair and ultimate regeneration still represents one of the main challenges of modern medicine. Indeed, cardiovascular disease can derive from independent conditions upsetting heart structure and performance: myocardial ischemia and infarction (MI), pharmacological cardiotoxicity, and congenital heart defects, just to name a few. All these disorders have profound consequences on cardiac tissue, inducing the onset of heart failure over time. Since the cure is currently represented by heart transplantation, which is extremely difficult due to the shortage of donors, much effort is being dedicated to developing innovative therapeutic strategies based on stem cell exploitation. Among the broad scenario of stem/progenitor cell subpopulations, foetal and perinatal sources, namely amniotic fluid and term placenta, have gained interest due to their peculiar regenerative capacity, high self-renewal capability, and ease of collection from clinical waste material. In this review, we will provide the state-of-the-art on fetal perinatal stem cells for cardiac repair and regeneration. We will discuss different pathological conditions and the main therapeutic strategies proposed, including cell transplantation, putative paracrine therapy, reprogramming, and tissue engineering approaches.